THE INFLUENCE OF SHARIA COMPLIANCE, PROMOTION AND REPUTATION OF BANK SYARIAH INDONESIA ON CUSTOMER LOYALTY - Sabardin (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2023)
Introduction: This study aims to investigate how customer loyalty of the Indonesian Sharia bank KCP Kuala Tungkal is affected by Sharia compliance, promotion, and reputation in various contexts or settings and various variables, such as various bank types or regions, which can affect the results. Methods: In this study, secondary data were analyzed using multiple regression with quantitative descriptive techniques using Eviews 10. The sample consisted of 99 respondents, all of whom were customers of Bank Mandiri Syariah. Results: The findings indicated that customer loyalty was not positively impacted by Sharia compliance; however, customer loyalty was positively impacted by reputation promotion, and reputation had a significant impact on customer loyalty. Additionally, there was a significant impact on customer loyalty when Sharia compliance, promotion, and bank reputation were combined. Conclusion and suggestion: There is a positive correlation between reputation and customer loyalty. This suggests that customer loyalty also increases as brand familiarity increases. This study contributes to consumer loyalty by promoting Sharia compliance, bank advertising, and reputation.